Extraction and integration of data entities on the web - Huang, Zhuqing (2014)
As the use of the Internet among people increases, location-based search services have become more and more common as well. Location-based search services are services that associate the geographical location of an entity with its non-spatial information (such as name, phone number, etc.). This brings convenience to users who can easily access the information of any entity near them. In Singapore, there are also many location-based search services, such as HungryGoWhere, Yelp and Foursquare. However, it is unlikely that all the available services will have exactly the same information, and so, for convenience of the user as well as to save space, it is beneficial to integrate data from multiple sources.